Feasibility of an electrostimulation system treatment for wound healing: a case series of patients with chronic ulcers in Barbados. Issue 6 (10th March 2015) - Ojeh, Nkemcho; Rose, Angela; Jackman, Selma; Applewhaite, Morvillia; Webster, Veronica
Abstract: Major advances have been made in the development of new therapies for chronic wounds. Fenzian™, an electrostimulation system (ES), has been clinically used for a variety of conditions. The ES was recently tested in the Barbadian population for tolerability and acceptability by asthma patients, with encouraging results. Barbados has an estimated 170 people with diabetes having some form of lower‐extremity amputation annually. Here, we describe a case series of 21 chronic ulcer patients with diabetes recruited as inpatients ( n = 10) and outpatients ( n = 11) in a pilot study to evaluate the feasibility and acceptability of ES in the Barbadian population. Results showed statistically significant improvement among those in the inpatient‐ versus outpatient‐recruited group for wound perimeter ( P = 0·04), wound surface area ( P = 0·03) and wound volume ( P = 0·08). We also demonstrate that the improvement continued after cessation of ES treatment. Participants reported increased levels of pain at the end of treatment, and there was no statistically significant change in the reported quality of life. Our results showed greater improvements in reduction of ulcer size for participants from the inpatient‐ versus outpatient‐recruited group.